2016
DOI: 10.1016/j.seizure.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

The burden of headache in people with epilepsy

Abstract: People with epilepsy experience headaches irrespective of their sex or age. The burden of headaches is very important in patients with epilepsy, since headaches usually cause a moderate or severe burden to their quality of life and suggest a clear clinical need. Clinicians should recognize headache as a common comorbidity of epilepsy, as it may influence antiepileptic drug choice, and may need specific treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
1
22
2
2
Order By: Relevance
“…In patients experiencing solely interictal headaches, 47% of their headaches were migraine type, and 41.5% TTH, although about 11.8% of headaches could not be classified in this group. In previous studies, the frequency of interictal headaches in patients with epilepsy was reported in the range of 19.3% to 77.9% [8,[13][14][15][16][17][18]. Our inability to establish the period in which patients with headaches in multiple periods experienced headaches more often could be the reason for our detecting a lower rate of interictal headaches compared with previous studies.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In patients experiencing solely interictal headaches, 47% of their headaches were migraine type, and 41.5% TTH, although about 11.8% of headaches could not be classified in this group. In previous studies, the frequency of interictal headaches in patients with epilepsy was reported in the range of 19.3% to 77.9% [8,[13][14][15][16][17][18]. Our inability to establish the period in which patients with headaches in multiple periods experienced headaches more often could be the reason for our detecting a lower rate of interictal headaches compared with previous studies.…”
Section: Discussioncontrasting
confidence: 57%
“…In our study group, 56.4% of patients had headaches. The rate of experiencing headache was reported in the range of 22% to 83.2% in patients with epilepsy [5,8,[12][13][14][15][16][17][18]. The differences in age groups, diagnostic and classification criteria, and the methodology used in the target population could explain this wide range of percentages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, depression and migraines remain undertreated in the US population and are infrequently addressed within the neurologic clinic, in particular in the pediatric population . Not surprisingly, these 2 comorbid disorders of epilepsy have been associated with a worse quality of life in PWE …”
Section: Complex Relation Between Common Psychiatric Comorbidities Anmentioning
confidence: 99%
“…For instance, the migraine aura is considered to occur over a longer period than the epilepsy aura. Moreover, previously published studies stated that migraine and tension‐type headache are the most frequently diagnosed headache conditions coexisting with seizure …”
mentioning
confidence: 99%